If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(v + 2) + -2v = 2(2v + 4) + -11 Reorder the terms: 6(2 + v) + -2v = 2(2v + 4) + -11 (2 * 6 + v * 6) + -2v = 2(2v + 4) + -11 (12 + 6v) + -2v = 2(2v + 4) + -11 Combine like terms: 6v + -2v = 4v 12 + 4v = 2(2v + 4) + -11 Reorder the terms: 12 + 4v = 2(4 + 2v) + -11 12 + 4v = (4 * 2 + 2v * 2) + -11 12 + 4v = (8 + 4v) + -11 Reorder the terms: 12 + 4v = 8 + -11 + 4v Combine like terms: 8 + -11 = -3 12 + 4v = -3 + 4v Add '-4v' to each side of the equation. 12 + 4v + -4v = -3 + 4v + -4v Combine like terms: 4v + -4v = 0 12 + 0 = -3 + 4v + -4v 12 = -3 + 4v + -4v Combine like terms: 4v + -4v = 0 12 = -3 + 0 12 = -3 Solving 12 = -3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| (((6.3*x)+(70*12.9))+66)-(31*6.8)=2154 | | 16-(r/7)=21 | | 0.25xY=23 | | F=4log(x/10^-5) | | z^4=6z^2+27 | | -36/15 | | x/0.55-2x | | (-1/12-7/3)/3/13 | | 16+x=-13 | | (-a-4b+2)ab= | | -11=x+22 | | 5a*6=120 | | x^1/4-1=0 | | (((4.3*x)+(70*4.7))+655)-(31*4.7)=2154 | | (((4.3*x)+(71*4.7))+655)-(31*4.7)=2154 | | 3.14=9420 | | 9+2s-7=9s+3-6s | | (((4.3*x)+(70*4.7))+655)-(30*4.7)=2154 | | a-7=-11 | | 4x^2-13x-36=0 | | -4(t-5)-(t+8)=5 | | 14--8/8 | | 15/18-18/19 | | 15/19-18/19 | | sin*2x+sin*8x=0 | | 10(v+2)-2v=2(4v+1)-4 | | 10x+5=10x+6 | | ×=-6/2 | | 4(5x-5)=-20(x-1) | | 6+2+3t+17=10 | | -5/8X-8-7 | | 12=11y-8y |